Assessment of the association between drug disposal practices and drug use and storage behaviors - AKICI, AHMET (ELSEVIER, 2018)
Objective: Keeping unnecessary drugs at home is a situation showing both causes and consequences of irrational use of medicine. This study aimed to evaluate the approaches of a company's employees regarding drug storage, use, and disposal. Method: This online-based descriptive study was held in a multi-centered private-sector company in a voluntary basis. The survey assessing participants' drug handling and storage behaviors was answered by 1121 employees from across eight provinces of Turkey in 2016. Main outcome measures were storage and disposal of unused/unwanted drugs at home in a rational way. Results: The percentage of participants who declared that they keep unused/unwanted drugs at home was 28.0%. About one-third of participants disposed their unused/unwanted drugs via the garbage, sink, toilet, etc.. Participants >= 30 years old and living with < 4 household members significantly tended to bring their unused/unwanted drugs to the company's drug-box. Nearly half of all participants (46.5%) stated a recent change in their disposal behavior. The vast majority of participants (94.6%) who previously took drugs back to the company's drug-box stated that they either had, or would, help their contacts adopt such behaviors. These participants were also significantly less likely to dispose of drugs inappropriately, practice self-medication, be unaware of expired drugs at home, or fail to store drugs according to the labelling. Conclusion: While our findings showed that a substantial number of participants still had unused drugs at home and disposed of them inappropriately, it is understood that they started to exhibit more favorable behaviors in recent years. (C) 2017 The Authors. Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Rational use of medicine; Drug handling; Drug storage; Drug disposal; Self-medication; UNUSED MEDICATIONS; SELF-MEDICATION; MEDICINES; PHARMACIES; FREQUENCY; KNOWLEDGE